Dynamic task allocation: how and why do social insect workers take on new tasks?. (December 2019) - Leitner, Nicole; Dornhaus, Anna
Abstract : Complex living systems often exist in noisy environments and must have a way to respond to change. In social insects, the colony itself is a complex system composed of dozens to millions of essentially autonomous workers. Studying the behaviour of these workers in response to experimental disturbance provides insight into the mechanisms by which colonies, and complex systems in general, can achieve flexibility. Here, we explore dynamic task allocation within colonies of Temnothorax rugatulus ants by separately increasing the demand for three different types of work: nest maintenance, brood care and foraging. We investigate (1) whether colonies respond to dynamic task demand and the timeline of their responses, (2) whether the colony achieves this flexibility by recruiting new workers to these tasks or modulating individual worker effort and (3) the rules by which individual workers switch tasks. We found that T. rugatulus ants are responsive to colony perturbation, yet the means by which they achieve this flexibility are task dependent, as is the time it takes them to respond. Flexibility is achieved both by the increased effort of already active workers and the recruitment of new workers to the focal task. We suggest that newly recruited workers may come from task-specific reserve pools of unemployed workers: roaming 'walkers' appear to be a generalized reserve force for most tasks except for brood care, while previously inactive workers might act as a specialized reserve pool for brood care and be prompted to engage in this task when they locally encounter brood. Highlights: We explored responses of T. rugatulus to changes in task demand. Responses to increases in demand for different tasks were dynamic and specific. Worker reallocation was task specific as were strategies used to match task demands. Two task-specific pools of workers appear to act as reserves for changes in workload. One pool appears to be more specialized in terms of which tasks it attends to.